Anthocyanin–aluminium and –gallium complexes in aqueous solution - Elhabiri, Mourad (1997)
Complexation of aluminium and gallium ions with synthetic anthocyanin models and natural anthocyanins extracted from the blue flowers of Evolvulus pilosus cv ‘Blue Daze’ and the violet flowers of Matthiola incana has been thoroughly investigated in aqueous solution. From UV–VIS spectroscopic data collected at pH 2–5, the presence of complexes, involving not only the coloured forms but also the colourless forms of the pigments is demonstrated. A theoretical treatment is developed for the calculation of the corresponding stability constants. The pigments studied throughout this work can be divided into two series, one sharing a cyanidin chromophore and the other a delphinidin one. Within both series, individual pigments are distinguished according to the degree and type of glycosylation and/or acylation. Intramolecular effects such as copigmentation of anthocyanin–aluminium complexes and the effect of the presence of a malonyl group on the formation of those complexes are discussed. These results are important to plant pigmentation and, for instance, a narrow pH domain in which colour amplification due to complexation is at a maximum has been found.